Guide to the Services Trade Restrictions Database - Borchert, Ingo; Gootiiz, Batshur; Mattoo, Aaditya (World Bank, Washington, DC, 2012)
A new Services Trade Restrictions Database collects and makes publicly available information on services trade policy assembled in a comparable manner across 103 countries, five sectors (telecommunications, finance, transportation, retail and professional services) and the key modes of service supply. It contains richly textured policy information as well as a preliminary quantification of policy measures. This paper is a guide to the database, and provides a description of the data, how it was collected, how policy information was quantified, and how the data are presented in the publicly available, interactive Web database. The database is best seen as a first response to the strong demand for better information from policy-makers, negotiators, researchers and the private sector. Even in its present version, the database can play an important role in advancing policy reform by facilitating the analysis of services policies, informing international negotiations by providing data on actual policies, and provoking dialogue and refinements by making information on policies publicly available. Through feedback from various interested parties, the database may evolve into a collectively created public good.